Between Medieval Archaeology, Heritage Protection and Archaeological Management: A Conversation with the Prof. PhD Albinas Kuncevičius - Merkevičius, Algimantas (Archaeologia Lituana, 2017)
With this conversation we aim to introduce to our readers one of the most well-known present-day Lithuanian archaeologists – Prof. PhD Albinas Kuncevičius, who heads the Archaeological Department at Vilnius University and whose 60th anniversary was commemorated at the end of this year. This conversation also discusses some issues important to the entire archaeological field of Lithuania. Keywords: Medieval Archaeology, heritage protection, Vilnius University, Dubingiai Castle, Vilnius Lower Castle, archaeological management